The Impact of Learning Goal Orientation and Psychological Safety on Learning Agility among Indonesian Management Trainees - Frida Zakiyya Harasuna (PSIKODIMENSIA Kajian Ilmiah Psikologi, 2025)
The increasing complexity of today’s work environment requires individuals to develop rapid and adaptive learning capabilities. This study aims to analyze the influence of learning goal orientation on learning agility among management trainee in Indonesia, and to examine the moderating role of psychological safety. A quantitative approach was employed with 300 management trainees from six industrial sectors. Data were collected via online questionnaires and analyzed using Moderated Regression Analysis (MRA). Results indicate that both learning goal orientation and psychological safety positively affect learning agility, but psychological safety does not moderate the relationship between them.  The practical implication highlights the importance of fostering psychologically safe workplaces and promoting a learning-oriented mindset to strengthen adaptive capabilities within organizations.